Nucleation events and metastable zone width of mefenamic acid polymorph in ethyl acetate - Abdul Mudalip, Siti Kholijah; Abu Bakar, Mohd Rushdi; Jamal, Parveen; Alam, Md. Zahangir; Adam, Fatmawati (Medwell Journals, 2017)
Understanding of the nucleation events and metastable zone width are essential in the crystallization process. This study investigates the use of cheap process analytical technology tools namely conductivity in comparison with the turbidity system for in-line detection of polymorph nucleation event in the solution crystallization. The effects of different cooling rates and initial concentrations on Metastable Zone Width (MSZW), nucleation kinetics and polymorphism of mefenamic acid in ethyl acetate solution were analyzed. The MSZW data and nucleation kinetics parameter were estimated based on the recorded nucleation temperatures. The recorded nucleation temperatures based on in-line conductivity data are in agreement with the in-line turbidity system. The MSZW was found to increase with the increase of cooling rates and decrease with the increase of saturation concentration. The nucleation order and nucleation rate constant kn calculated from MSZW data using Nyvlt classical theory varied with the initial solution concentration. The highest solution concentration which was 3.6/100 g ethyl acetate, shows highest (0.1460) and lowest n (4.1374) values. This indicates fast nucleation at higher solution concentration. The crystallization using different cooling rates does not show significant effect on the final polymorphs chemistry where mefenamic acid Form I was produced.